1979
DOI: 10.1111/j.1365-2141.1979.tb03761.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 5‐Fluorouracil on Mouse Bone Marrow

Abstract: 5-Fluorouracil (150 mg/kg) was injected intravenously into 11-week-old male mice. Its effects on marrow structure over the following 9 d were assessed using light microscopic examination of semi-thin transverse sections of decalcified humeri. The extravascular compartment became markedly depleted of cells and decreased in size, reaching a minimum on day 5 post-treatment. Proliferating haematopoietic cells disappeared within 2 d. Post-replicative erythrocytic cells underwent extra-vascular phagocytosis by resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 32 publications
3
26
0
Order By: Relevance
“…Furthermore, expansion of Mk during platelet recovery was not accompanied by changes in ECM components distribution and contents. In contrast, the experiments demonstrated that on day 10 post-5-FU administration, Mks occupied most of the extravascular space within BM, with other myeloid cells almost absent [42]. These events were accompanied by an increase in BM content of ECM components and followed by peripheral platelets count recovery simultaneous with the regeneration of BM vasculature as described by Kopp et al [43].…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, expansion of Mk during platelet recovery was not accompanied by changes in ECM components distribution and contents. In contrast, the experiments demonstrated that on day 10 post-5-FU administration, Mks occupied most of the extravascular space within BM, with other myeloid cells almost absent [42]. These events were accompanied by an increase in BM content of ECM components and followed by peripheral platelets count recovery simultaneous with the regeneration of BM vasculature as described by Kopp et al [43].…”
Section: Discussionmentioning
confidence: 80%
“…Utilizing the well‐described hematopoietic recovery following 5‐FU injection [17, 18], we previously demonstrated that nine days following 150 mg/kg 5‐FU, platelets and femoral CFU‐Meg in rhG‐CSF‐treated splenectomized B 6 D 2 F 1 mice were significantly lower than in non‐rhG‐CSF‐treated controls, indicating an inhibitory influence of rhG‐CSF on megakaryocytopoietic recovery [16]. Interestingly, the beneficial effect of eight days of continuous rhG‐CSF on granulopoiesis resulting in an accelerated recovery of blood granulocytes was not observed when rhG‐CSF administration was delayed for five days.…”
Section: Discussionmentioning
confidence: 99%
“…37 Hematopoietic recovery from 5-FU is dependent, in part, on the regenerating properties of quiescent HSCs that are induced to divide and differentiate in the immediate aftermath of 5-FU treatment. 38 Although progenitor or other non-HSC defects can also result in increased sensitivity to 5-FU, defects in HSC representation or function have been associated with increased 5-FU sensitivity in some contexts.…”
Section: Impaired Survival Of Mll5 ؊/؊ Mice Injected With 5-fumentioning
confidence: 99%